From Common Market to Emu: A Historical Perspective of European Economic and Monetary Integration - Philip Arestis; Kevin McCauley; Malcolm Sawyer (Levy Economics Institute of Bard College, 1999)
This paper traces the history and the institutional background of European integration to the establishment of the economic and monetary union in the European Union (EU). After the establishment of the European Economic Community (EEC) in the late 1950s, attempts at monetary integration, and ultimately monetary union, tended to assume importance only as a result of financial crisis and then returned to being a vague objective as soon as the crisis recedes. In recent years, however, monetary integration has assumed greater urgency. Economic union, on the other hand, has followed a smoother transition. Economic integration was used after the Second World War to realize political goals, chiefly to anchor West Germany within the western European alliance. Since that time the economies of member states have slowly integrated. The economic environment of the 1950s is a far cry from the integrated community of today. In the 1950s European currencies were not convertible and domestic trade was highly protected. Intra-European trade was based on bilateral clearing arrangements institutionalized by the European Payments Union. Today EU currencies are fully convertible; capital controls, intra-EU tariffs, and quotas have been eliminated; and the single market has been completed. Monetary union has gone through a number of stages. The Werner Plan of the early 1970s, which set the goal of economic and monetary union by the end of the decade, was only partially implemented. Its failure can be put down to unfavorable international economic conditions and poor institutional structures. In the early 1980s a new monetary initiative, the European Monetary System (EMS), was launched. It struggled through its initial phase until it was replaced by the current euro arrangements. These successive stages ultimately culminated in the Maastricht Treaty, which laid out a precise path and timetable for economic and monetary union.
Keywords: 330